EGZEMPCJE WOJSKOWE - IMMUNITET ŻOŁNIERSKI W RZECZYPOSPOLITEJ SZLACHECKIEJ XVI-XVII WIEKU - Łopatecki, Karol (Zeszyty Prawnicze, 2017)
Military Exemptions - Soldier’s Immunity in Polish -Lithuanian Commonwealth of XVI-XVII Century Summary Military exemptions have not been described in the hitherto literature whereas they constitute an interesting phenom enon allowing to evaluate the legal position of mercenary soldiers, functioning of legal norms of a temporary character and the interrelations between the statutory and customary law. In XVI and XVII centuries both - general exemptions, granted by Seym, and hetm an’s exemptions, deprived of the Seym’s sanction, existed. The constitutions on the exemptions always had a temporary nature. As a consequence o f the advancing paralysis of the parliament’s works, the exemptions issued by hetm an became more and more common. Exemptions were the releases to be applied before all types of courts, apart from military courts. They withheld the proceedings (even enforcement proceedings when the verdict did not benefit from the res iudicata character) with regard to all persons taking part in the military expeditions and their families. This enhanced the attractiveness of military service and prevented soldiers from leaving the army. Exemptions were known to the customary law, however, they were formulated by Seym by means of constitutions. The parliament, depending on the circumstances, enlarged or limited the group of the beneficiaries, applied more or less strict criteria, changed the time limits of the exemptions’ validity, prevented their abuse, and most importantly, it firmly opposed a rejection of the releases by courts.